2007
DOI: 10.1101/lm.437407
|View full text |Cite
|
Sign up to set email alerts
|

Implicit probabilistic sequence learning is independent of explicit awareness

Abstract: Studies into interactions between explicit and implicit motor sequence learning have yielded mixed results. Some of these discrepancies have been attributed to difficulties in isolating implicit learning. In the present study, the effect of explicit knowledge on implicit learning was investigated using a modified version of the Alternating Serial Response Time (ASRT) task, a probabilistic sequence learning paradigm that yields continuous and relatively pure measures of implicit learning. Results revealed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
145
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(165 citation statements)
references
References 55 publications
18
145
2
Order By: Relevance
“…For example, when learning was assessed in young adults across three sessions with equivalent intervals of wakefulness or sleep, Song et al (2007) andHoward, 1997, Romano, Howard, and, they found no sequencespecific improvements from an a.m. to p.m. session or a p.m. to a.m. session. Similarly, when Nemeth and Janacsek (2011) tested participants on probabilistic sequence learning, before and after a 12-hr, 24-hr, or a 1-week interval, they found an improvement in general motor skill (i.e.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…For example, when learning was assessed in young adults across three sessions with equivalent intervals of wakefulness or sleep, Song et al (2007) andHoward, 1997, Romano, Howard, and, they found no sequencespecific improvements from an a.m. to p.m. session or a p.m. to a.m. session. Similarly, when Nemeth and Janacsek (2011) tested participants on probabilistic sequence learning, before and after a 12-hr, 24-hr, or a 1-week interval, they found an improvement in general motor skill (i.e.…”
Section: Introductionmentioning
confidence: 97%
“…Sequence-specific learning refers to faster responses as a result of the acquisition of sequence-specific knowledge. Many serial reaction time task (SRTT) studies to date have not distinguished between these two components of performance (but see Hallgato et al, 2013;Németh et al, 2010;Song, Howard, & Howard, 2007, for exceptions).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations